Penerapan Model Pembelajaran Project Based Learning Untuk Meningkatkan Kemampuan Berfikir Kreatif Siswa Pada Tema 7 Peristiwa Dalam Kehidupan - Tri Putri Naomi; Dewi Anzelina; Novalina Sembiring; Reflina Sinaga; Ester Julinda Simarmata (Departement of Mathematics Education, 2023)
The learning process runs well if it can properly consider various related elements, including: goals, materials, and methods in learning. In order to achieve success in the learning process, it also needs other support, namely the teacher can combine elements related to learning and student behavior. As is the case at this time students are required to be able to think creatively. Based on observations made in class VB SD HKBP Padang Bulan Medan, obtained a number of information that became a problem including in learning activities carried out by teachers already using learning models in learning activities, but teachers have not developed creative thinking skills to students. To overcome these problems, one way that can be taken is to update the learning model that is commonly used. An active learning model that is considered suitable to be used to improve students' thinking skills is the Project Based Learning learning model. Based on the results of the research and discussion, it can be concluded that the use of the Project Based Learning model on the theme of events in the fifth grade of SD HKBP Padang Bulan Medan can improve the creative thinking ability of students so that it reaches the target of classical completeness. Out of 29 students, students' creative thinking skills at the initial stage, namely in the pre-test, there was an average score of 57 with 20% classical completeness. In cycle I, it increased with an average score of 66 with 48% classical completeness. Furthermore, in cycle II, the average creative thinking ability of the students was 80 with 80% classical completeness, meaning that the presentation of students who experienced changes was more than 75%. This shows an increase from cycle I to cycle II.